CHINESE STUDENTS’ METAPHORICAL DESCRIPTIONS OF THAI TEACHERS AT A THAI UNIVERSITY (Malaysian Journal of Learning and Instruction, 2022)
Purpose – This paper discusses Chinese students’ negative and positive written feedback about Thai teachers using metaphorical descriptions and the links between it and their classroom experiences.Methodology – An open-response questionnaire was employed to collect the data from 21 Chinese female students. The questionnaire provided both positive and negative “people” or “thing” metaphors of Thai teachers for students’ selection. In addition, students were allowed to use their own metaphors to describe their teachers. Data was analyzed by using open and axial coding techniques.Findings – The results revealed that Chinese students were able to compare Thai teachers with either a “person” or “thing” metaphor and could write a metaphorical description that reflected different aspects of their instructors’ teaching, both positively and negatively. The quality of their descriptions was rich enough to link with their classroom learning experiences. Both positive and negative “people” and “thing” metaphorical descriptions were associated with three different viewpoints: academic, power dynamics, and emotion. The positive “people” metaphorical descriptions were linked to four classroom issues: knowledge and experience, teaching style, motivation, and guardian/protector. In contrast, the positive “thing” and negative “people” and “thing” metaphorical descriptions were linked to three classroom issues: knowledge and experience, teaching style, and emotion.Significance – These findings help to strengthen Thai-Sino understanding of the relationship between Chinese students and Thai teachers. Findings also suggested that Chinese students’ metaphorical feedback should be used with the non-metaphorical assessment form to evaluate and improve Thai teachers’ instructional practices in the Thai-Chinese student exchange curriculum.